PENGARUH EKUITAS MEREK DAN WORD OF MOUTH TERHADAP KEPUTUSAN NASABAH UNTUK MENABUNG DI BANK BRI CABANG S. PARMAN BENGKULU - Veny Puspita (Creative Research Management Journal, 2020)
The purpose of this study was to determine the composition of brand equity and word of mouth for customer decisions regarding deposit accounts at BRI Bank Parman Bengkulu. The nature of this research is associative. In accordance with the nature of this study, two types of qualitative data and quantitative data. Research data sources: primary data and secondary data. Respondents in this study are those who have savings at Bank BRI Parman Bengkulu. Data collection techniques using a questionnaire and the data obtained were analyzed using. Research Results The brand equity variable and Word of Mouth has influence both partial and simultaneous on the customer's decision to save. It should be like that